Comparative corporate governance and international portfolios. Issue 8 (14th July 2016) - Giofré, Maela
Abstract : The impact of foreign investor protection on portfolio choices negatively depends on the degree of domestic investor protection enjoyed by the investor. The coefficient of foreign countries' investor protection scaled by world average is therefore not constant across investing countries. The ratio foreign to domestic investor protection rights index is shown instead to be a plausible common driver of international portfolios. Phrased differently, domestic investor protection replaces the world average corporate governance in the construction of the relevant measure driving international portfolio choice. If the weight attached to the domestic factor in the construction of the average measure is large enough it can determine, almost completely, the world average corporate governance. This outcome is consistent with a setting in which the investor, strongly hit by information constraints, places a disproportionally large weight on domestic information considered as more reliable because observed at a higher precision.